2005
DOI: 10.1038/sj.eye.6701830
|View full text |Cite
|
Sign up to set email alerts
|

Lower eyelid tensometry in younger and older normal subjects

Abstract: Purpose This study aimed to establish normative and repeatability data for lower eyelid tensometry (LET) using a newly developed eyelid tensometer. Methods In this prospective consecutive observational case series, 32 normal adult subjects, comprising 12 younger (aged 2975 years, 6M : 6F) and 20 older subjects (aged 7476 years, 10M : 10F), underwent LET. In the younger group, LET was measured for posteroanterior (PA), nasal and temporal displacement. Duplicate measurements were taken and these were repeated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Eyelid tension or pressure has been measured by different instruments, [13][14][15][16] and although the instruments were different for each laboratory, there was general agreement that the eyelid tension or pressure decreased with increasing age in normal eyes as was found in our normal subjects. Interestingly, this significant decrease in the eyelid pressure was not found in the patients with dry eye.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Eyelid tension or pressure has been measured by different instruments, [13][14][15][16] and although the instruments were different for each laboratory, there was general agreement that the eyelid tension or pressure decreased with increasing age in normal eyes as was found in our normal subjects. Interestingly, this significant decrease in the eyelid pressure was not found in the patients with dry eye.…”
Section: Discussionmentioning
confidence: 55%
“…12 Since then, eyelid tension or pressure has been measured by various instruments that measure the tension of the eyelid on the ocular surface. [13][14][15] However, a standardized method of measuring the eyelid tension or pressure has not been established because the methods and measuring devices were not easy to use and were not accurate.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] King and Michels 19 as well as Martin 20 measured the muscular tension by electromyographic methods during blinking, although they focused on the changes of muscular tension at different blink rates under different psychological conditions. [15][16][17][18][19][20] King and Michels 19 as well as Martin 20 measured the muscular tension by electromyographic methods during blinking, although they focused on the changes of muscular tension at different blink rates under different psychological conditions.…”
mentioning
confidence: 99%
“…4,13 It explains why older individuals had a lower rate of LWE, as aging is linked to decreased lid pressure from the decline in muscle tone of the orbicularis oculi and involutional changes to collagen, elastin, and glycosaminoglycan in the eyelid. 37,49,50 It would explain why females were found to have a lower severity in LWE, as Francis et al 51 have found that females have lower lid tension than males. Finally, it could explain why Asians were nearly twice as likely to present with LWE than non-Asians and have a greater severity in LWE length and width, as the distinctive ocular anatomy in Asians, having greater herniation of orbital fat and smaller palpebral aperture size, may collectively contribute to greater lid pressure.…”
Section: 13mentioning
confidence: 82%